PENGARUH PENGGUNAAN MEDIA SOSIAL YOUTUBE TENTAN ROASTING BEBERAPA PEJABAT DALAM STAND-UP COMEDY PADA PEMBELAJARAN MENULIS TEKS BIOGRAFI SISWA KELAS X SMK PGRI 2 BELITANG - Haryadi Haryadi; Gunawan Ismail; Ernita Sari (MEDAN MAKNA: Jurnal Ilmu Kebahasaan dan Kesastraan, 2022)
The purpose of this research is to describe the effect of using YouTube social media about roasting several officials in stand-up comedy on the learnining of wriinge biographical texts for grade X students of SMK PGRI 2 Belitang. This reserch uses experimental method.  Samples are selected by using a simple random sampling technique, the samples are students of grade X.1 and X.4 amounting 51 students. The data of this study are obtained through test techniques, questionnaires and interviews with Indonesian teachers who teach in grade X SMK PGRI 2 Belitang. Based on the results of the research description, the result of a significance value of 0.000 which means 0.000 <0.05 so Ho is rejected and Ha is accepted, it means that YouTube social media about roasting some officials in stand-up comedy is effectively used in the learning of writing biographical texts. Thus, it is concluded that "the influence of using YouTube social media about roasting several officials in stand-up comedy on the of writing biographical texts for grade X students of SMK PGRI 2 Belitang" is influential and proven true.